2007
DOI: 10.1007/bf02980264
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of inducible prostaglandin E2 production and cyclooxy-genase-2 expression by curdione fromCurcuma zedoaria

Abstract: Overproduction of prostaglandins has been considered in mediation of inflammation and carcinogenic process. On this line, the inhibitors of prostaglandin biosynthetic enzyme cyclooxygenase (COX) have played a role of anti-inflammatory and cancer chemopreventive agents. In our continuous efforts to search anti-inflammatory and chemopreventive agents from natural products, bioassay-guided fractionation led to the isolation of curdione from the rhizome of Curcuma zedoaria with the inhibitory effect on the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Curdione belongs to the family of monocyclic monoterpenes with one ring in the isoprene chain. Curdione was found to inhibit the production of PGE2 in LPS‐stimulated mouse macrophages through the suppression of COX‐2 expression .…”
Section: Anti‐inflammatory and Anticancer Activities Of Noncurcumin Cmentioning
confidence: 99%
“…Curdione belongs to the family of monocyclic monoterpenes with one ring in the isoprene chain. Curdione was found to inhibit the production of PGE2 in LPS‐stimulated mouse macrophages through the suppression of COX‐2 expression .…”
Section: Anti‐inflammatory and Anticancer Activities Of Noncurcumin Cmentioning
confidence: 99%
“…Plant rhizome has also used as a carminative, digestive stimulant and for treatments of colds and infections (Prajapati et al 2003). In addition, the rhizome has also been intensively used as a traditional medicine in China for the treatment of cancer (Oh et al 2007). Curcumin and curcumenol, chemical compounds of this plant were reported to inhibit growths of S-180 sarcoma cells and mouse cervical U-14 cells (Lai et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…7) could suppress the 12-O-tetradecanoylphobol-13-acetate (TPA) -induced inflammation of mouse ears by 75% and 53%, respectively, at dose of 1.0 µmol (Makabe et al, 2006). Oh et al (2007) used bioassay-guided fractionation which led to an isolation of curdione from the rhizome of C. zedoaria with the inhibitory effect on the production of PGE2 in LPS-stimulated mouse macrophage RAW 264.7 cells in a concentrationdependent manner (IC 50 = 1.1 µM). Jang et al (2004) reported active compounds, 1,7-bis(4-hydroxyphenyl)-1,4,6-heptatriene-3-one, procurcumenol, and epiprocurcumenol, isolated from C. zedoaria which inhibited the NO production in LPS-activated macrophages.…”
Section: Chemical Constituents and Anti-inflammatory Activity Of Prasmentioning
confidence: 99%